Pengaruh Pengetahuan Dan Motivasi Terhadap Minat Investasi Mahasiswa Untuk Berinvestasi Dipasar Modal Syariah - Fitri Finalti; Putri Apria Ningsih; Khairiyani Khairiyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Sulthan Thaha Saifuddin Jambi State Islamic University is one of the campuses that has an Investment Gallery which is used as a medium for investing in stocks in the capital market. However, student investment interest is still very low.Knowledge and motivation are important elements to start investing. This study aims to determine and analyze the influence of knowledge and motivation on interest in investing in the Islamic capital market in students who open stock exchange accounts at UIN STS Jambi. The method used in this study is a quantitative method, and the data analysis method used is the coefficient of determination test. The sample in this study was 89 samples of UIN STS Jambi students, by distributing Likert scale questionnaires. The results of this study indicate that knowledge influences the investment interest of UIN Sulthan Thaha Saifudin Jambi students. Motivation influences the interest in investing in UIN Sulthan Thaha Saifuddin Jambi students. Knowledge and motivation jointly affect the interest in investing in students of UIN Sulthan Thaha Saifuddin Jambi.